Changes in social relationships by the initiation and termination of public assistance in the older Japanese population: A JAGES panel study. (January 2022) - Kino, Shiho; Nishioka, Daisuke; Ueno, Keiko; Saito, Masashige; Kondo, Naoki
Abstract: Public assistance recipients in Japan are financially empowered by social welfare but are also exposed to social stigma. Therefore, when their status of receiving public assistance changes, the conditions of their social life likely change. We examined whether the social relationships of older adults receiving public welfare are influenced by either starting or terminating their use of public assistance. This study used the Japan Gerontological Evaluation Study panel data from 2013 to 2016. To measure social relationships, we used four indicators: the frequency of meeting with friends, the number of friends whom the participants had met with in the past month, their frequency of participating in sports clubs, and their frequency of participating in hobby clubs. In the analyses, changes in social relationships between 2013 and 2016 were used as the study outcomes. Linear regression analyses were conducted to examine if their social relationships changed before and after starting or terminating public assistance while adjusting for confounders. We found that people who stopped receiving public assistance experienced an increase in their frequency of meeting with friends (coefficient: 0.56; 95% CI: 0.06, 1.07), the number of friends (coefficient: 0.60; 95% CI: 0.20, 0.99), participation in sports clubs (coefficient: 0.91; 95% CI: 0.46, 1.39), and participation in hobby clubs (coefficient: 0.70; 95% CI: 0.26, 1.13) compared to those who continued to receive public assistance. Contrarily, the measured social relationships did not change after the participants started receiving public assistance. Our main findings were that terminating one's reception of public assistance increases informal socializing and social participation while starting public assistance does not interrupt pre-existing relationships. These findings contribute to the literature by adding that social relationships are not negatively influenced by either terminating or starting public assistance. Targeted promotions of social connections would effectively maintain the health statuses of low-income older adults. Highlights: People who stop receiving public assistance more frequently meet with friends. When people stop receiving public assistance, their number of friends increases. People participate more frequently in social clubs once they stop receiving welfare. Starting to receive public welfare does not impact one's pre-existing.